2011
DOI: 10.4093/dmj.2011.35.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Heme Oxygenase-1 on High Glucose-Induced Pancreatic β-Cell Injury

Abstract: BackgroundGlucose toxicity that is caused by chronic exposure to a high glucose concentration leads to islet dysfunction and induces apoptosis in pancreatic β-cells. Heme oxygenase-1 (HO-1) has been identified as an anti-apoptotic and cytoprotective gene. The purpose of this study is to investigate whether HO-1 up-regulation when using metalloprotophyrin (cobalt protoporphyrin, CoPP) could protect pancreatic β-cells from high glucose-induced apoptosis.MethodsReverse transcription-polymerase chain reaction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…Few controversies exist regarding that the toxicity of glucolipids to pancreatic ␤-cells and their involvement in ␤-cell apoptosis (1)(2)(3)26). With advances in the understanding of the pathogenesis of T2D, RAGE has garnered attention as a circulating protein that is cytotoxic, resulting in pancreatic ␤-cell apoptosis (4, 6 -8, 10).…”
Section: Discussionmentioning
confidence: 98%
“…Few controversies exist regarding that the toxicity of glucolipids to pancreatic ␤-cells and their involvement in ␤-cell apoptosis (1)(2)(3)26). With advances in the understanding of the pathogenesis of T2D, RAGE has garnered attention as a circulating protein that is cytotoxic, resulting in pancreatic ␤-cell apoptosis (4, 6 -8, 10).…”
Section: Discussionmentioning
confidence: 98%
“…Among them, the most representative are the pro-apoptotic (Bax) and anti-apoptotic (Bcl-2) genes [36]. Recent studies have demonstrated that exposure to high glucose or FFA levels may induce apoptosis in pancreatic cells [37,38]. In the present study, we analyzed the effect of PSG-1 on the histology of pancreatic cells and evaluated the expression of Bax and Bcl-2 in pancreatic tissues of type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cobalt protoporphyrin, a known Hmox-1 inducer, protected INS-1 β -cells from high glucose-induced oxidative stress and apoptosis; however, it failed in restoring the GSIS in these cells [39]. The latter indicates that the mechanisms underlying the protective effect of SFN against the pancreatic β -cells dysfunction induced by cholesterol are beyond Nrf2 pathway induction and oxidative stress inhibition.…”
Section: Discussionmentioning
confidence: 99%